Outcome of recurrent and metastatic head and neck squamous cell cancer patients after first line platinum and cetuximab therapy. (June 2017) - Siano, Marco; Infante, Gabriele; Resteghini, Carlo; Cau, Maria Chiara; Alfieri, Salvatore; Bergamini, Cristiana; Granata, Roberta; Miceli, Rosalba; Locati, Laura; Licitra, Lisa; Bossi, Paolo
Highlights: We report outcome for second line treatment after anti-EGFR-AB and platinum. Response rate was low, median OS higher than expected in anti-EGFR-AB naïve pts. Only half of the pts with r/mHNSCC were able to receive 2nd-line treatment. Response to first line treatment predicts better prognosis. Our real-life data is important for future trials in second line treatment. Abstract: Objectives: Second-line chemotherapy in recurrent and/or metastatic head and neck cancer (r/mHNSCC) patients showed dismal results with limited tumor response and reduced life expectancy. Outside of clinical trials, data on efficacy of second line treatment after first line anti-EGFR-AB combination therapy are not available. Material and methods: Data regarding r/mHNSCC consecutive pts treated with cetuximab and platinum from 2009 to 2014 at our center were retrospectively collected. The analyses of response, Progression-Free Survival (PFS) and Overall Survival (OS), each evaluated starting from first and second-line treatment, were performed. Survival curves were estimated with the Kaplan-Meier method and compared using the log-rank test. Results: We identified 117 patients treated with first-line platinum and cetuximab-based therapy. Sixty-four (55%) patients did not receive second-line treatment due to worsening in performance status, 2 were not assessable for response thus 51 patients were included for analysis. Fifty-six percent were smokers/former smokers and 78% were male. Primary tumor sites were oropharynx (39%), oral cavity (31%), larynx/hypopharynx (24%) and others (6%). Regimens used in second-line were mostly monotherapies. Twenty-one % of the patients were treated within a clinical trial. Response rate (PR, CR) was 6% with 45% showing SD as best response. Median PFS was 2.2 months (95%CI:1.5–2.8 months) and OS 6.1 months (95%CI:3.7–7.2 months). Conclusions: Within our single center experience only half of the patients with r/mHNSCC were able to receive second-line treatment. Response rate was unsatisfactory, but median OS seems higher than previously reported in an anti-EGFR-AB naïve population (Leon 2005).